PENINGKATAN KETERAMPILAN BERBICARA SISWA MENGGUNAKAN METODE LATIHAN BERBICARA DI KELAS III - Julia, Kristina; Halidjah, Siti; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to determine the improvement of speech skill of students by used speaking skill’s method on grade III Elementary School 01 Seluas Bengkayang. The research method that been used was descriptive method. The type of this research was Classroom Action Research which was four stages that was planning, acting, observing and reflecting .This research was done in 3 cycles. The results of research were obtained (1) The ability of teacher to arrange learning draft from cycle I was 3,71 in cycle II was 3,9 and cycle III was 3,98. The ability of teacher to do learning showed increase from cycle I 3,47, cycle II was 3,78, and cycle III was 3,98. The average of speech skill of students increased from cycle I with score 79,56 became 87,13 in cycle II and became 97,33 in cycle III. The using of speaking skill’s method increased the speech skill of students. Keywords: Speech Skill and Speaking Skill’s Method